Analysis Concept of Hyperrealism in Harry Potter’s Novel by J.K Rowling - Masdalena Masdalena; Ilham Saputra (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The aims of this article are to analysis concept of Hyperrealism in Harry Potterâ€™s Novel by J.K Rowling. There are about 7 novels from J.K Rowling that tell about life in a witch school (Hogwarts) which is filled with mystery and friendship between Harry Potter as the main character, of course with different series in each of the stories. The analysis method used in this novel the title is Harry Potter because the researchers would analyze concept of hyperrealism used in the novels. The process of this article has several step such as read the novels, identifies a concept of hyperrealism, making table to collect about concept of hyperrealism and the last is to evaluate the concept. This article is to help readers more easily understand a concept, namely the concept of hyperrealism in Harry Potter stories.Keyword: Â Hyperrealism, Harry Potter, J.K Rowling